Antioxidant activity of aqueous extract of Sonchus arvensis L. in-vitro - Sofnie M. Chairul; Ros Sumarny; Chairul . (Indonesian Journal of Pharmacy, 2003)
Antioxidants are the compounds which have ability to inhibit reactive oxygen species (ROS) and free radicals in human body. Based on this activitiy the antioxidants prevent cell damage and various pathological processess e.q. cardiovascular, diabetes mellitus, atherosclerosis, respiratorydiseases, carcinogenesis, inflammation, cell degenerative. One of the famous Indonesian traditional medicine is tempuyung or S. arvensis L.(Asteraceae). The antioxidant test has been conducted on the dried water extract by measuring the peroxide value (POV) and in-vitro antioxidant activity test was carried out by spectrophotometry applying thiocyanate method at the wave length of 500 nm.The results showed that peroxide value of dried water extract of tempuyung (S. arvensis L. ) by titration iodometric method has a lower value (865.60) compared to positive control -tocoferol (1142.77). In-vitro antioxidant activity test has remarkable results at the various extract concentrations (1, 5 dan 10 %) and had significant differential absorbance(A) with positive control (K+) as well as negative control (K-), and among the extract concentrations (P  0,5). Absorbance value increased along with increasing storage time, in which negative control reached higher value of A (0,987) in the seven days and maximal value after eight days (A  1), while the absorbance value of positive control (K+) was 0.648, and dried water extract of tempuyung 1, 5 & 10 % was 0.576, 0.488 & 0.314 after 14 days, respecticly. The absorbance value of absorbance (A) was inversely compared to extract concentrations. Increasing of extract concentrations resulted in decreasing A value, in other words increasing extract concentration resulted in the increas of antioxidant activity.Key words : Sonchus arvensis L, Asteraceae, POV, antioxidant, thiocyanate method.